STUDY ON REMOVAL MECHANISM OF SINGLE-CRYSTAL SILICON BY PLASMA DISCHARGE (MT) - ZHAI ZhiBo; LIU FeiFei; JIA GuoPing; XIN Bin; WANG YanHui (Jixie qiangdu)
Aiming at the problems of easy introduction of chemical element residues, micro scratches and low material removal rate in contact chemical mechanical polishing and non-contact plasma polishing processes of single-crystal silicon, a non-contact green polishing method of plasma cavitation stripping for single-crystal silicon is proposed. In the water-based working fluid medium with pulse voltage more than 100 V, the high impedance state isolation vapor layer breaks down due to the small curvature convergence of electron flux and induces an oxygen plasma channel. The convex position of the micro-region on the surface of the anode single crystal Si generates an SiO2 loose film due to the enhancement of the anode chemical reaction by the oxygen plasma. During the pulse intermission period, the plasma channel collapses due to the cold shock liquefaction of the water-based working fluid medium near the wall surface, and cavitation micro-jet impact force is formed at the same time to strip the loose film on a nano scale. After treating the sample for a certain time, the surface roughness of the sample can reach 1.54 nm, and no new chemical elements will be introduced into the surface of the sample. It provides a green non-contact method for plane/non-plane ultra-precision machining of brittle and hard materials.